Evaluation of geothermal potential in some parts of Bida Basin of Nigeria using Curie point depths and heat flow from spectral analysis of aeromagnetic data - Matthew Tersoo Tsepav; Abu Mallam (Universitas Sebelas Maret, 2020)
The Centroid method of Spectral Depth analysis was used to evaluate the Curie point depth (CPD), Geothermal Gradient and Heat Flow in some parts of the Bida Basin of Nigeria with a view to determining the energy potential of the area. The reduced-to-pole aeromagnetic data was divided into 16 overlapping ensembles and Fast Fourier Transformed to decompose the anomalies into their energy and wavenumber components using Oasis montaj software. The radial power spectrum was calculated for each of the grid points with the locations of the centres of the ensembles and a plot of Energy spectrum versus frequency was carried out to generate two different gradients: s1 and s2 representing different depth source models. These gradients were used to evaluate the average depth to the top of the deepest crustal block, Zt, depth to the centroid of the deepest crustal block, Z0, CPD, Geothermal Gradient and Heat flow. From the results obtained, the CPD varied from 2.59 to 8.23 Km while the thermal gradient and heat flow in the area revealed values ranging from 70.45 to 224.15 oCKm-1 and 176.13 to 560.37mWm-2 respectively. The results of the contouring in conjunction with the CPD, geothermal gradient and the heat flow values have shown that the area has a greater energy potential in the south-eastern block of Katonkarfi, with shallow CPD and high geothermal gradient and heat flow. These results could be incorporated in the GIS and available geological, geophysical and geochemical information of the area to facilitate selection of the optimum site for energy exploration.